2020
DOI: 10.3390/polym13010108
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of 3T3 Fibroblasts on PHB, PLA and PHB/PLA Blend Films at Different Stages of Their Biodegradation In Vitro

Abstract: Over the past century there was a significant development and extensive application of biodegradable and biocompatible polymers for their biomedical applications. This research investigates the dynamic change in properties of biodegradable polymers: poly(3-hydroxybutyrate (PHB), poly-l-lactide (PLA), and their 50:50 blend (PHB/PLA)) during their hydrolytic non-enzymatic (in phosphate buffered saline (PBS), at pH = 7.4, 37 °C) and enzymatic degradation (in PBS supplemented with 0.25 mg/mL pancreatic lipase). 3T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…It depends on the activity of various enzymes. According to Zhuikov et al, (2021) [27], enzymatic degradation is found to significantly accelerate the degradation rate of PLA I PHB compared to non-enzymatic hydrolytic degradation. The first reported PLA-degrading enzyme was proteinase K from Tritirachium album [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It depends on the activity of various enzymes. According to Zhuikov et al, (2021) [27], enzymatic degradation is found to significantly accelerate the degradation rate of PLA I PHB compared to non-enzymatic hydrolytic degradation. The first reported PLA-degrading enzyme was proteinase K from Tritirachium album [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Among these materials are biopolyesters, including polyhydroxybutyrate (PHB) and polylactide (PLA). These polymers are polyesters that are synthesized using bio-resources such as sugar or plant oil and are characterized by good biocompatibility, biodegradability, and sustainability, which make them a potential alternative for biomedical applications [3][4][5][6]. Biopolyesters can be modified via polymer-polymer blending, some of the commonly employed techniques include copolymerization, crosslinking, composition, and blends [7].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Ausejo and coworkers (2018) investigated the PLA/PHB blends for their improved utility properties and biodegradability for use in additive manufacturing-3D printing [13]. Besides, PLA, PHB, and their blends can be considered for important biomedical applications as the production of conventional medical implantation devices, tissues engineered and controlled drug delivery systems, including repair patches, drug delivery platforms, wound healing, and biocompatible sutures [6,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…PHB has been extensively considered for biomedical devices [22][23][24]. An example of this is the blends of PHB with hydroxyapatite that have been studied in tissue engineering and regenerative medicine applications [23].…”
Section: Introductionmentioning
confidence: 99%